Sistem Pakar Untuk Mengidentifikasi Hama Dan Penyakit Pada Tanaman Apel Menggunakan Metode Dempster Shafer - Muhammad Rizky Iman Permana; Yufis Azhar; Otto Endartoi (Jurnal Repositor, 2020)
In this study, the identification of pest and disease attack on apple plant on with case study in Balitjestro. The problem faced is the difficulty of determining the information of pests or diseases that attack on apple plants that must meet an expert directly, it takes a long time and cost. The purpose of this study is to accelerate the information obtained from the identification of pests and diseases of the apple plant and its solution without having to meet an expert. Types of pests and diseases that is in pests are Green Lice, Mites, Trips, Leaf Cats, Leaf Sucking Insects, Black Leaf Caterpillars and Fruit Flies. In the disease there are Flour Powder, Leaf Spot, Upas Mushroom, Cancer and Rotten Fruit. From pest and disease data, all symptom data is 38 data. To get the information, made Expert System. Expert system in this study to determine the results of identification using Dempster Shafer calculation method. Demster Shafer is one of the mathematical theories used to perform a proof that is based on the function of trust and also logic makes sense. At the test stage yields an accuracy value of 100%. However there is one test of the expert only producing one and the results of the system show more than one. But one of the results given by the system is the same as the result given by an expert, then it is justified.